Transforaminal Percutaneous Endoscopic Lumbar Diskectomy for Downmigrated Disk Herniations: Lever-Up, Rotate, and Tilt Technique - Eun, Sang Soo; Lee, Sang-Ho; Erken, H. Yener (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Study Aims Although transforaminal percutaneous endoscopic lumbar diskectomy (PELD) offers certain advantages in the treatment of disk herniations, it used to be limited to nonmigrated or low-migrated herniations. With improvements in endoscopic spinal surgery, the range of indications for PELD has expanded. Various techniques including transforaminal and interlaminar approaches for migrated disk herniations are described in the literature. This study describes a transforaminal PELD approach to address downmigrated intracanal soft disk herniations effectively using the lever-up, rotate, and tilt technique.Patients and Methods We performed a retrospective review of 18 patients who had been operated on with the described technique between October 2012 and December 2015. We assessed clinical outcomes using the visual analog scale (VAS) for back and leg pain and the Oswestry Disability Index (ODI) preoperatively at their respective clinical visits and postoperatively at the patients' final follow-up examinations.Results The mean preoperative VAS scores for back and leg pain were 3.75 + 1.34 (range: 2–6) and 8.3 + 0.6 (range: 8–10), respectively. The mean preoperative ODI was 67.3 + 15.3 (range: 48–90). The mean VAS scores for back and leg pain improved to 1.38 + 1.58 (range: 0–6) and 1.19 + 0.75 (range: 0–3), respectively, at the last follow-up. The mean ODI also improved to 14.1 + 6.2 (range: 8–30) at the last follow-up. All differences between the preoperative and last follow-up scores were statistically significant (p < 0.05), Two surgeries failed because of a remnant disk fragment.Conclusions The lever-up, rotate, and tilt technique for transforaminal PELD is an effective maneuver to treat downmigrated disk herniations in selected patients by experienced surgeons.
Keywords: lever-up; rotate; tilt; PELD; endoscopic lumbar diskectomy